Improving Learning Creativity in Early Childhood Through Learning Media Loose Part: Energetic, Concentrated and Creative - Sumarmi Sumarmi; Achmad Ruslan Afendi (EduLine: Journal of Education and Learning Innovation, 2022)
Loose Part Media is an effective learning method that can increase children's creativity. This paper aims to test loose part media can increase learning creativity in early childhood. This study uses a qualitative approach with a descriptive method. Data collection methods used are observation, short interviews, and documentation. Sources of data obtained from children's play activities and children's work are documented directly as the main informant and explained using children's stories. The subjects of this study were early childhood, as much 15 people. Research data processing is carried out systematically so that the effectiveness of the data can be used to draw conclusions. The results of this study indicate that the application of loose-part media is proven to be effective in increasing the creativity of early childhood learning. This can be seen from the behavior shown by children in learning activities using loose part media, namely energetic, concentration, and creative. Loose-part media also encourages children to build knowledge around them through observing, asking questions, investigating, and solving their own problems, it will increase children's creativity when they play. Loose part media is media that is always used by teachers in the teaching and learning process in the classroom. This is due to its flexibility in every lesson, its ease in using in games, and is liked by children. In addition, this loose part of media also gives freedom for children to express their ideas, creativity, and imagination in activities through these media.